Exploring trial publication and research waste in COVID-19 randomised trials of hydroxychloroquine, corticosteroids, and vitamin D: a meta-epidemiological cohort study - Lisa Fincham; Ameer Hohlfeld; Mike Clarke; Tamara Kredo; Michael McCaul (BMC Medical Research Methodology, 2024)
Abstract Background The global research response to the COVID-19 pandemic was impressive, but also led to an infodemic and considerable research waste. Registered, but unpublished trials added to this noise. We aimed to determine the proportion of registered randomised trials of common COVID-19 treatments that were published and to describe the characteristics of these trials to examine the association between trial characteristics, publication status and research waste. Methods This meta-epidemiological cohort study used a sample of randomised trials of corticosteroids, hydroxychloroquine or vitamin D as treatments for COVID-19, registered between 1 November 2019 and 31 December 2021 and available via the WHO ICTRP portal. We searched for the trials’ published results up to 20 October 2022. We extracted the trial characteristics, analysing with descriptive statistics. We performed univariate logistic regression to examine the association between trials’ characteristics and publication status, followed by multiple logistic regression using significant characteristics to assess the association between trial characteristics and publication status. Results We identified 357 eligible trials on ICTRP. Of these, 107 (30%) had published or made their results available publicly by 20 October 2022, while 250 (70%) had not been published or shared their results publicly. Multiple logistic regression analysis showed that a larger target sample size was a significant positive predictor of publication with target sample sizes above 300 almost tripling the odds of publication (aOR: 2.75, 95% CI: 1.35 to 5.62). Conclusions Less than one third of registered trials made their results public and our findings identified that many trialists had not updated their trial registry entry with the trial status, results or both. Failure to share trial results publicly is a disservice to patients, clinicians and policy makers and adds to research waste.